2015
DOI: 10.1214/15-ejs988
|View full text |Cite
|
Sign up to set email alerts
|

The rate of convergence for approximate Bayesian computation

Abstract: Approximate Bayesian Computation (ABC) is a popular computational method for likelihood-free Bayesian inference. The term "likelihoodfree" refers to problems where the likelihood is intractable to compute or estimate directly, but where it is possible to generate simulated data X relatively easily given a candidate set of parameters θ simulated from a prior distribution. Parameters which generate simulated data within some tolerance δ of the observed data x * are regarded as plausible, and a collection of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 25 publications
1
85
0
Order By: Relevance
“…In particular, it can be shown that the bias of the ABC estimate is asymptotically proportional to h 2 , as h → 0. On the other hand, the computational cost for generating n accepted ABC samples is proportional to nh −q , where q is the dimension of the observations (Barber et al, 2015). The same authors show that the mean squared error (MSE) of the estimates for constant expected computational costs is given by…”
Section: Likelihood-free Methodsmentioning
confidence: 99%
“…In particular, it can be shown that the bias of the ABC estimate is asymptotically proportional to h 2 , as h → 0. On the other hand, the computational cost for generating n accepted ABC samples is proportional to nh −q , where q is the dimension of the observations (Barber et al, 2015). The same authors show that the mean squared error (MSE) of the estimates for constant expected computational costs is given by…”
Section: Likelihood-free Methodsmentioning
confidence: 99%
“…The discrepancy threshold determines the level of approximation, however, under the assumption of model and observation error, Equation (31) can be treated as exact [151]. [9,40]. Using data for the monomolecular chain model, we can demonstrate this convergence, as shown in Figure 4 (see also Appendix D).…”
Section: Likelihood-free Methodsmentioning
confidence: 80%
“…Through application of the ABC with acceptance threshold, , the equivalent marginals are p(k 1 | ρ(Y obs , S obs ) ≤ ) = Reducing further than 12.5 is prohibitive, even for the mono-molecular chain model. Both Barber et al [9] and Fearnhead and Prangle [40] provide an asymptotic result for the computation time, C, as a function of , that is, C = O( −d ), where d is the dimensionality of the data used in the ABC inference. For the synthetic data we have from Table C.1, we have d = n t N .…”
Section: Appendix D Additional Abc Resultsmentioning
confidence: 99%
“…A formal treatment of the issue is given by Blum (2010), Barber et al (2015) and Biau et al (2015) amongst others.…”
Section: Summary Statisticsmentioning
confidence: 99%